-: - - Dien, Ina Triesna Budiani (EMARA: Indonesian Journal of Architecture, 2025)
Population growth in Indonesia is still relatively high compared to Sub-Urban (rural) areas at around 96% per year. Based on the 2015-2045 population projections from the 2015 Inter-Census Survey (Supas), Indonesia's population would reach 269.6 million people in 2020. The United Nations Population Fund (UNFPA) had a death rate (mortality) of 1.6 million people in 2019 and will continue to increase by 2045 by 3.2 million people. Tombs/graves are included in the City Green Open Space (GOS) category. As of 2016, Indonesia had 249.2 hectares of green open space, which included parks, farms, and tombs/graves. Considering the anticipated high death rate, it required a considerable area of tombs/graves. A minimum of 20 hectares of land had to be set aside for tombs/graves in Medan City, one of the cities in Indonesia. The city administration is currently attempting to add graves in marsh areas, water bodies, former rice fields, and other locations in collaboration with the Parks Service. Such land conditions, however, are not yet ready-to-use land. Also, the site is situated on the city's outskirts. The cemetery in the center of Medan is where locals are used to interring their relatives. Considering the lack of urban land designated as tombs/graves, the solution is to create multilevel tombs/graves (Multi-Storied Cemeteries). Multilevel graves, specifically grave that, depending on the shape of the burrow, can hold 4-6 bodies in one hole, the height of the groundwater from the location of the graves, and especially the height of the groundwater level, which must be measured using a Web-based Pantir (Water Monitoring) tool Mobile. To count the number of graves in a cemetery, it is necessary to measure the height of the groundwater level. By creating a multi-storied cemetery, the number of tombs in each cemetery in the city area could be decreased.